Beyond spontaneity: unveiling the organized dynamics of mob violence in Pakistan = Keinerlei Spontaneität: Organisierten Dynamiken von Mobgewalt in Pakistan - Kakar, Ayesha (Kriminologie - das Online-Journal, 2025)
This research article attempts to elucidate the recurrent nature of mob violence from 2010-2024, focus-ing on key elements such as preplanning, coordination, organizational control, and leadership. Through a purposive sampling technique, a diverse-case study approach is employed to examine the factual con-texts and emerging patterns of mob violence incidents in Pakistan. The study aims to offer an insight into the nature and circumstances of such occurrences across various regions of Pakistan by examining n=25 sample cases. The findings reveal that mob violence is a more organized and structured form of violence, characterized by societal endorsement, contrary to the historically perceived spontaneous out-bursts. Moreover, the study highlights how different societal factions (religious and political) strategi-cally exploit mob violence to achieve ulterior objectives. The research concludes by emphasizing the need for policy interventions, both administrative and legislative, to effectively curb the occurrence ofmob violence in Pakistan.